Carriage trends and fitness cost of MDROs in Lebanese nursing homes - Caren Challita; Nourhane Hafza; Elias Dahdouh; Michel Attieh; Iman Dandachi; Ziad Daoud (Journal of Infection in Developing Countries)
Introduction: Nowadays, medical treatments efficiency is challenged by multi drug resistant organisms (MDROs). Lebanese nursing homes’ residents revealed high fecal carriage rates of MDR Enterobacteriacea. Previous studies claim that bacteria with resistant genes experience fitness cost. This study assesses the competitive growth of MDR Escherichia coli and Klebsiella pneumoniae.